Economic Valuation of a Protected Mangrove Forest in Southern Cebu, Philippines - ROSE JANE C. ROSALES; LORENCE R. LIBRANZA; JADA FRANCINE Z. ROBLE; FLORY MAY B. JUCDONG; MARINELLE C. JUMAWAN; SARAH EMPEÑO; CHERRY M. FLORES; JASON DUMDUM; SYLVESTER T. CORTES; ZERRY AYN Z. RETUBADO; ANNE S. LORCA; JOSEPH JOEL N. ALMAGRO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Rosales RJC, Libranza LR, Roble JFZ, Jucdong FMB, Jumawan MC, Empeño S, Flores CM, Dumdum J, Cortes ST, Retubado ZAZ, Lorca AS, Almagro JJN. 2025. Economic valuation of a protected mangrove forest in Southern Cebu, Philippines. Biodiversitas 26: 1491-1502. Mangroves are important ecosystems due to their roles in coastal protection, nurseries, carbon sequestration, and other services. However, climate change, habitat destruction, and aquaculture expansions threaten these ecosystems in the Philippines. Thus, this study investigates the Total Economic Value (TEV) of mangroves in Argao, Cebu, Philippines, which is a coastal municipality with a mangrove ecosystem spanning over 130.52 hectares across eight coastal barangays, to contribute to their conservation efforts. Argao has a wide cover of mangroves and most of the locals depend on the mangrove's ecosystem services and resources. Through an in-depth semi-structured interview survey using snowball sampling, data was gathered from 406 direct users. Use values, classified into direct (such as fishing, gleaning, etc.), indirect (such as coastal protection, carbon sequestration, etc.), and optional (such as ecotourism, goat feed, etc.) benefits, were assessed in addition to non-use values which include existence and bequest values. The economic valuation strategies and analysis involved a combination of market valuation, replacement cost, travel cost, benefit transfer method, and contingent valuation. The calculated TEV of mangroves was Php 307,487,030.00 or USD 5,227,279.51 annually, with use values dominating at 98.9%. This significant economic value underscores the importance of mangroves to the local economy. While non-use values at 1.01%, it also reveals the importance of mangroves to biodiversity preservation, landscape appreciation, research, and others. The study also reports the factors affecting mangrove conservation in the area, namely coastal development, aquaculture expansion, climate change, community livelihood dependency, and insufficient local awareness. Some conservation strategies are relative to these limiting factors. The study concludes that mangroves in the area provide ecological and economic benefits, thus urging the local government units and resource users to implement conservation strategies to achieve long-term sustainability and prosperity for the local environment and the community.